PENELITIAN ASPEK PERKOTAAN DUMAI DAN BITUNG DAN KEMUNGKINANNYA SEBAGAI LOKASI KAWASAN EKONOMI KHUSUS DI INDONESIA - Edyanto, CB Herman (Jurnal Sains dan Teknologi Indonesia, 2009)
Special Economic Zone has been introduced as a new approach in Indonesia for regional development purposes on the basic of economic activities concentration. Some countries have run such project as part of national income and thus opening new job opportunity for the local people. A concept for its development need to be established since it also affects to the government’s expenditure. This is a chance for the government to open mind in creating new investment from other countries to Indonesia. Two cities have been chosen as cases of study namely Bitung – north Sulawesi Province and Dumai – Riau Province. The first is known as fish processing industry city whereas the second one is known as CPO processing industry city. This study has proved that Dumai has a good prospect as a special economic zone based on the application of Powersim dynamic programming model for its analysis.